2014
DOI: 10.18052/www.scipress.com/etet.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying Processes on Stability of Anthocyanin Extracts from Saffron Petal

Abstract: ABSTRACT. Saffron (Crocus sativus) has cyanic color flowers with major colorant of anthocyanin. Attractive color and functional properties of anthocyanins make them a good substitute for synthetic pigments in the food industry. These natural soluble water colorants are rather unstable and influenced by final processing treatment. The drying process is critical to the stability of saffron petals anthocyanins. Four different dehydration methods were evaluated: traditional method (at room temperature and under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…But, high share of producing saffron is exclusively dedicated to producing and drying saffron stigmas whereas their violet color petals are mostly ignored and get disposed of. In the meanwhile, saffron petal is one of the most economical sources of anthocyanin pigments (Hemmati Khakhki, 2001;Heydari et al, 2014 ;Nørbaek, Brandt, Nielsen, Ørgaard, & Jacobsen, 2002;Williams, Harborne, & Goldblatt, 1986). Attractive color and functional properties such as antimicrobial properties, antiemetic, antipyretic, anti-itch, anti-inflammatory, hypertensive, antiarrhythmic (irregular heartbeats), sedative, analgesic, and antioxidant properties of anthocyanins can make them a good substitute for synthetic pigments in the food industry (Castañeda-Ovando, de Lourdes Pacheco-Hern andez, P aez-Hern andez, Rodríguez, & Gal an-Vidal, 2009;Kafi, 2006;Khosrokhavar, Ahmadiani, & Shamsa, 2010).…”
mentioning
confidence: 99%
“…But, high share of producing saffron is exclusively dedicated to producing and drying saffron stigmas whereas their violet color petals are mostly ignored and get disposed of. In the meanwhile, saffron petal is one of the most economical sources of anthocyanin pigments (Hemmati Khakhki, 2001;Heydari et al, 2014 ;Nørbaek, Brandt, Nielsen, Ørgaard, & Jacobsen, 2002;Williams, Harborne, & Goldblatt, 1986). Attractive color and functional properties such as antimicrobial properties, antiemetic, antipyretic, anti-itch, anti-inflammatory, hypertensive, antiarrhythmic (irregular heartbeats), sedative, analgesic, and antioxidant properties of anthocyanins can make them a good substitute for synthetic pigments in the food industry (Castañeda-Ovando, de Lourdes Pacheco-Hern andez, P aez-Hern andez, Rodríguez, & Gal an-Vidal, 2009;Kafi, 2006;Khosrokhavar, Ahmadiani, & Shamsa, 2010).…”
mentioning
confidence: 99%
“…As Table shows, increasing temperature (even 10 °C) decreased drying time substantially; so, 80 °C resulted in the shortest drying time. Heydrai, Rezaei, and Haghayegh (), studying the effect of different drying processes on stability of anthocyanin extracts from saffron petal, reported that microwave drying shortened process duration from 40 min for oven drying (80 °C) to 16 min at microwave powder of 180 W and 6 min at microwave power of 900 W. However, it has been demonstrated now that microwave drying, especially at high powers, could bring about irreversible color and physicochemical changes in the final product (Orsat, Changrue, & Raghavan, ).…”
Section: Resultsmentioning
confidence: 99%
“…Irrigation management of saffron consists of six applications: in the middle of summer, the second in early October, the third in November, the fourth in late December, the fifth in early March, and the sixth in early April. After 180 days from the sowing date (October), tepals were separated by hand shortly after collecting in the field and were dried, in the dark, for 8–10 days, by the traditional methods at room temperature to avoid the degradation of the main bioactive molecules [ 21 ]. After drying, the tepals were crushed and stored at -20°C until use—the same harvesting and drying method was repeated in the same site's 2019 harvest plots.…”
Section: Methodsmentioning
confidence: 99%